An architecture for managing schema evolution in a federated spatial database system - Wu, Xiaoying; Xia, Jianhong (Cecilia); West, Geoffrey; Arnold, L.; Veenendaal, Bert (WALIS, 2011)
A Federated Spatial Database System (FSDBS) is the integration of multiple spatial data sources and the realisation of effective spatial data sharing. FSDBS environments are becoming increasingly popular as more and more spatial and non-spatial datasets are integrated, especially those across a number of independent organisations. However, in a FSDBS environment, database schemas are subject to change and the management of these changes is complex and inefficient. This is because schema changes in one local database will affect or invalidate not only applications built against this local schema, but also applications built against the global schema. In this research, a Schema Element Dependency Meta-model and a set of Schema Change Templates which incorporates view generation, view rewriting and query rewriting have been developed as the solution in managing schema evolution in a FSDBS. This paper focuses on the architecture of Automatic Schema Evolution that includes a schema element dependency tool, a schema mapping tool and a view rewriting tool. These tools are embedded with the developed methods will assist in effective management of schema evolution in a FSDBS and engendering collaboration and interoperability between data custodians and application developers and users.